Application of response surface methodology to optimise supercritical carbon dioxide extraction of essential oil from Cyperus rotundus Linn - Wang, Hongwu; Liu, Yanqing; Wei, Shoulian; Yan, Zijun (Food chemistry, 2012)
► SC-CO2 extracted essential oils from Cyperus rotundus. ► Effects factors were investigated by response surface methodology. ► The oil yield was represented with central composite rotatable design. ► Pressure and CO2 flow rate are the main effects factors. ► Oil yield of C. rotundus was significantly higher than that of Soxhlet extraction. Supercritical fluid extraction with carbon dioxide (SC-CO2 extraction) was performed to isolate essential oils from the rhizomes of Cyperus rotundus Linn. Effects of temperature, pressure, extraction time, and CO2 flow rate on the yield of essential oils were investigated by response surface methodology (RSM). The oil yield was represented by a second-order polynomial model using central composite rotatable design (CCRD). The oil yield increased significantly with pressure (p<0.0001) and CO2 flow rate (p<0.01). The maximum oil yield from the response surface equation was predicted to be 1.82% using an extraction temperature of 37.6°C, pressure of 294.4bar, extraction time of 119.8min, and CO2 flow rate of 20.9L/h.